Relationship between Caries Experience and Food Intake with Stunting Among 6-8-Years Old of Elementary School at Pantai Labu District in 2018 - Ester Afsani Simorangkir; Sondang Pintauli; Etti Sudaryati (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Stunting is one of major problem in the world, including Indonesia. Its prevalence 30.8% in 2018. It is a chronic growth faltering caused by low food intake and long-term disease makes child shorter than the average of the same age. The objective of the research was to assess the relationship of caries experience and food intake with stunting in 6-8 years-old elementary school children in Pantai Labu District in 2018.The research used a cross-sectional approach. The samples were 144 aged 6-8 years-old, taken by using a cluster sampling technique. Stunting was assessed by measure the value of height to age, caries experience was measured by using the def-t index and food intake were calculated by using food recall 24 hours. The data were analyzed by using the Chi-square test and multiple logistic regression tests. The result of this study indicated that stunting children occurred due to high caries experience (52.4%) and low protein intake (54%). The result of Chi-square test showed that there was the relationship of caries experience (p=0.004; PR=2.150, CI=1.216-3.799), and protein intake (p=0.001; PR=2.376, CI=1.338-4.219) with stunting. The result of multiple logistic regression tests indicated that low protein intake the most dominant correlate with stunting (p=0.001; PR=3,950, CI=1.725-9.405). The conclusion was high caries experience and low protein intake was risk factor for stunting. Stunting in children is 3 times comes from low protein intake and have a chance about 89% causing stunting compared to good protein intake.